Impact of Executive Functions and Parental Anxiety on the Development of Social Cognition in Premature Children: A Cross-Sectional Case-Control Protocol - Eutrope, Julien; Novo, Alexandre; Barbe, Coralie; Loron, Gauthier; Rolland, Anne-Catherine; Caillies, Stéphanie (Frontiers in Psychiatry, 2021)
Background: Recent research has identified neuropsychological disorders, specifically executive function disorders, in premature children. Executive functions support goal-oriented mental activity and play a role in the development of social cognition. This underlies the social and emotional behavior of individuals. Parental anxiety is also an important environmental factor that can influence the psycho-emotional development of children. Objectives: The present protocol aims to compare the development of social cognition in school-age children born prematurely to that of school-age children born full-term, and to determine the impact of executive (dys)function and parental anxiety on such development. Methods/Design: In this cross-sectional protocol, 28 prematurely born children aged 7-10 years (“preterm”) and 28 full-term born children aged 7-10 years (“control”) will be included. The “preterm” and “control” groups will be matched for sex and age. The neuropsychological evaluation will include that of non-verbal intellectual efficiency (Raven's colored progressive matrices), verbal level (WISC-IV subtests), and executive functions (NEPSY II subtests and the opposite worlds of TEA-CH). The evaluation of social cognition will be conducted via tests of the theory of cognitive and affective mind. Several dimensions of the level of parental anxiety will be collected through the Spielberg Trait Anxiety Inventory Form Y, Beck Depression Inventory, Social Support Questionnaire-6, Parental Stress Index and, specifically for mothers, the Modified Perinatal Post-Traumatic Stress Disorder Questionnaire. Discussion: The results of this protocol will aid our understanding of the development of social cognition in premature children and to determine the factors that influence such development. This clinical research project, although following a fundamental approach, will have clinical implications because a more precise description of the development of social cognition in this school-age population will make it possible to better determine the cognitive targets of therapeutic actions and to search for predictive indices of the efficacy of practices. Trial Registration:https://clinicaltrials.gov/ct2/show/NCT03007095, identifier: NCT03007095.